O jornal Imprensa Evangelica e as origens do protestantismo brasileiro no século XIX - Santos, Silas Daniel dos (2018)
In the second half of the 19th century, with the arrival of the Rev. Ashbel Green Simonton (1859) sent missionary as by the Protestant mission of the Presbyterian Church of the United States of America (PCUSA), caused significant transformations in the religious context and culture of Brazil. In 1864, Simonton and other missionaries, created the newspaper denominated of Press Evangelica. In analyzing the creation, dissemination and diffusion of the Imprensa Evangelica newspaper, the first Protestant Portuguese-language newspaper published in Brazil published biweekly from 1864 to 1892 in Rio de Janeiro, we saw that the Protestant missionaries of PCUSA gave the printed word a value extraordinary, which would then become an efficient ally of the ideal of spreading and disseminating the Protestant faith in national territory. They also made use of the printed word for the circulation of information on the missionary activities of PCUSA and the doctrinal instruction of the faithful through reading the Bible and a vast Protestant literature. The missionaries of PCUSA long ago wanted to find a Protestant periodical to support instruction to the newly converted and their children. Its editors initially intended a weekly, but they gave up after the publication of issue number 1. They then published it every two weeks on the first and third Saturdays of each month. For 28 years, in those days when Protestantism was implanted in Brazil, the Evangelical Press was the official organ of the Presbyterian Church in Brazil. Considered the most complete document of the social changes proposed by the new denomination from the middle of the XIX Century. The Evangelical Press became the great integrator of the Protestant Churches in Brazil. It served as a contact between Presbyterians and Brazilian elites. He fought for religious freedom, denounced the mistreatment and persecution of the Roman Church. I brought several texts and literary genres. He published the translation of various classics of worldly Protestant literature and disseminated throughout the country the doctrines of the Reformed faith. It was fruitful in publishing Bible studies. It was read, respected and recognized by the elites of Brazilian society. However, the vast majority of the Brazilian population was illiterate and their minds were not open to the written word. The Evangelical Press introduced in Brazil from the missionaries the habit of reading.